Desenvolvimento de um protótipo de identificação das linhas de ônibus no transporte coletivo - Anjos, Rodrigo Ferreira dos (2018)
Microelectronics is an area of engineering that is linked to social inclusion and enables the construction of low-cost devices in order to provide more comfort and bring improvements to the daily lives of people with special needs. Most Brazilian cities do not offer specialized service in the identification of public transportation, for people who have weaknesses in the vision. With an electronic system to identify bus lines, it intensifies social inclusion and allows the user to have more security and autonomy when boarding a bus. In Jo˜ao Pessoa-PB, a group of students built a device for individual use, which makes the bus driver be aware that there is a visual deficiency at a certain point, in Natal-RN the city has installed plaques in Braille on the platforms with the lines which operate there. This paper presents a proposal for the identification of bus lines for collective use. The main objective is the direct interaction with passengers who need the bus identification service. The system has two devices, one installed in the bus and another at the point of shipment. The identification is by means of audio in speakers, informing the passengers, at the point, the name of the line of the approaching bus. The system communicates with each other through radio frequency antennas, each device receives a microcontroller, programmed to control the flow of information between buses and the point of shipment. The line of a bus is announced the moment the bus approaches the point, then this same line is skipped, for a certain time to avoid the traffic of repeated information. The system has been tested with carriage to measure the range of the antennas as well as the functionality of the program. The program met the design requirements, but the antennas did not meet the manufacturer’s reach specifications. A greater range of communication between systems can be achieved by replacing antennas with other models where the settings are easy to adapt to the source code, however, the system worked with good audio quality and no repetitions.